PENERAPAN PAKET TEKNOLOGI TEPAT GUNA DAN PEMANFAATAN LIMBAH UNTUK DIVERSIFIKASI PRODUK OLAHAN KELAPA - Parhusip, Bastian (Departemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Coconut has wide usability because apart from being a raw material for the food and non-food industries it is also ahousehold consumption. The utilization of coconut is not only as cooking oil but there are several other processed coconut products that are trading currencies in the international market, among others, shredded coconut, fresh coconut milk, shell charcoal, coconut sugar and virgin coconut oil or known as Virgin Coconut Oil (VCO). Pondos Village is located inWest Amurang District, South Minahasa Regency, North Sulawesi. This area has coconut plantation yields reaching20,000 grains / month. Through village-owned enterprises, the Pondos village government formed an IKM calledMapalus. This IKM has several problems including 1) coconut peeling is still manual using hands, the number of coconuts peeled every day ranges from 400-600 coconuts (12 hours of work), 2) coconut milk squeezing is still manualusing hands, 3) the coconut milk produced is not homogeneous so the quality is low, 4) the product has no laboratorytests on the chemical composition of coconut oil, 5) the results of coconut waste are not utilized, 6) There is noverification of processed coconut products. Based on the results of PKM activities held by the team, to increase productivity, quality of coconut processing and processing of coconut waste products, there are several activities carried out including: 1) the availability of a coconut peeling machine that can produce a minimum of 9600 coconuts in 8 hours of work every day, 2) There is coconutmilk squeezing equipment to facilitate the process of making processed coconut oil; 3) The existence of a centrifugationdevice to homogenize coconut milk and facilitate the separation of cream and skim; 4) Laboratory testing of the chemicalcomposition of coconut oil; 5) provision of marketing management training. The results of this activity increase theproductivity and economy of the community, especially IKM Mapalus Pondos